1977
DOI: 10.1084/jem.145.5.1176
|View full text |Cite
|
Sign up to set email alerts
|

Immunological studies of Aging. III. Cytokinetic basis for the impaired response of lymphocytes from aged humans to plant lectins.

Abstract: The basis for the age-associated defect in the response of lymphocytes to plant lectins has been studied. Using three independent assays we have shown that the number of mitogen-responsive cells is markedly reduced in lymphocyte preparations from old persons. In addition, studies using colchicine bloock and thymidine pulse techniques have revealed a failure of mitogen-responsive cells from old persons to expand into a proliferating pool of lymphocytes as is observed when lymphocytes from young persons are cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Third, the depressed PHA response of PBMC from subjects over 70 can be partly reversed by blocking the endogenous production of prostaglandin with the addition of indomethacin, a prostaglandin synthetase inhibitor. Aging is associated with depressed humoral and cellular immunity in man (9)(10)(11)(12)(13) and experimental animals (14)(15)(16), although in humans T-cell function (cellular immunity) seems more depressed than B-cell function (humoral immunity) (9). The cause of this Tcell dysfunction has not been determined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the depressed PHA response of PBMC from subjects over 70 can be partly reversed by blocking the endogenous production of prostaglandin with the addition of indomethacin, a prostaglandin synthetase inhibitor. Aging is associated with depressed humoral and cellular immunity in man (9)(10)(11)(12)(13) and experimental animals (14)(15)(16), although in humans T-cell function (cellular immunity) seems more depressed than B-cell function (humoral immunity) (9). The cause of this Tcell dysfunction has not been determined.…”
Section: Methodsmentioning
confidence: 99%
“…Normal aging mice have both increased suppressor cells (14)(15)(16) and decreased helper cells (14), whereas in man, the development of autoantibodies and monoclonal gammopathies with age would argue for loss of suppressor cell activity, at least in the humoral immune system (12,17). Recent work by Inkeles et al has demonstrated that the hyporesponsiveness of lymphocytes from aging humans to PHA is actually a sum of two deficiencies (10). First, the number of mitogenresponsive cells is reduced in lymphocyte preparations from old people.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that fewer T cells from elderly people acquire TCGF receptors of sufficient number or affinity to mediate a cellular response to TCGF. This may explain the presence of fewer mitogen-responsive lymphocytes in the blood of elderly people (3). There is no evidence that binding of PHA by lymphocytes from elderly mice is decreased with age (17).…”
Section: T Cell Growth Factor Production By Lymphocytes In Aged Humansmentioning
confidence: 99%
“…There is evidence that reduc tion in the size of the T-cell pool [8] and alter ation in the mechanisms that initiate T-cell activation or a reduction in the intrinsic ca pacity of individual T cells to enter into cell cycle, may account for the observed T-cell dysfunction [20]. Furthermore, in regard to the altered cell response to mitogens, Hefton et al [17] suggested the possibility of fewer mitogen-responsive cells due to the failure of aging cells to divide normally in culture.…”
Section: Discussionmentioning
confidence: 99%